Optimization of Implementation of Crane Certification in Contruction Service Companies - M Yusuf Arnol; Nyoman Gede Suryadharma; Manggi Dwi Cahyono; Dahrijoso Soejakti; Lalak Indiyono (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This study aims to analyze the effect of accelerating the implementation of work and the costs needed for the job of occupational safety and health certification in the Construction services company in East Java province. Design/methodology/approach: This study used a survey method carried out on 20 crane units in 4 construction service companies by analyzing data using Critical Path Method (CPM), resulting in an acceleration of inspection and testing of crane up to 37% with cost efficiency of 36 %. Findings: The results of this study are expected to provide an overview of Crane's reliability as early as possible to users to anticipate operational failures through regular maintenance and repairs. Research limitations/implications: This study can also determine the timing of inspection and testing in the context of implementing the Crane Occupational Safety and Health certification so that the use of resources can be optimized. Practical implications: With the implementation of inspection and testing, certification can be fulfilled before the certification period ends. Originality/value: This paper is original Paper type: Research paper